Perilaku Petani Hortikultura terhadap Paparan Pestisida - Murwanto, Bambang; Rosita, Yeni (Jurnal Kesehatan, 2022)
Horticultural crop farmers are a population at risk for pesticide poisoning, which in the long run will cause anemia. The purpose of the study was to determine the behavior of horticultural farmers in Gisting District, Tanggamus Regency in spraying pesticides. This research design uses a qualitative descriptive method with a phenomenological approach. Informants in this study were horticultural agricultural workers who were taken purposively in the production of horticultural crops, community leaders as well as agricultural and health officers, namely Pekon Campang, Gisting District, Tanggamus Regency. The interview technique used is Focus Group Discussion (FGD) or Terarah Group Discussion (DKT) for agricultural workers and in-depth. In principle, the behavior of farmers using pesticides is still not good, such as how to spray pesticides, including the management of used pesticide containers and not using proper Personal Protective Equipment (PPE). However, with the support of community leaders, including the head of the village (village), they made efforts to prevent poisoning. The health office should pay special attention to this area (Pekon Campang) for vulnerable groups such as pregnant women and toddlers who are at risk of being affected by pesticide poisoning, either directly or indirectly.